The Influence of Training and Job Placement on Innovative Work Behavior of Employees at Hotel Aston Manado - Sondakh, Kurnia; Rumawas, Wehelmina; Punuindoong, Aneke (Productivity, 2025)
In the hospitality industry, employees play a vital role in determining the quality of service provided to guests. Proper training and job placement are expected to influence the innovative work behavior of hotel employees along with the increasingly competitive industry. The purpose of this research is to find out how influential job training and placement are on the innovative work behavior of Aston Manado Hotel employees. This research uses quantitative research methods, with data collection methods using survey methods, namely questionnaires (Questionnaires), the sample in the study was 55 respondents. This research analysis tool uses Smart PLS 4.0 software. The results of this study indicate that training has no effect on innovative work behavior, training has a positive and significant effect on job placement, and job placement has a positive and significant effect on innovative work behavior.